The Integration Of Digital Marketing And Ecotheological Values In Export-Oriented Msmes To Access Global Markets - Nurul Khaerani, Siti (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to deeply understand the experiences of export-oriented MSME (Micro, Small, and Medium Enterprises) actors in implementing digital marketing and ecotheological values as strategies to enter the global market. Employing a qualitative approach with a phenomenological method, the research involved six MSMEs in Lombok and fourteen informants, consisting of business owners, production staff, and marketing personnel. Data were collected through in-depth interviews, non-participant observation, and field documentation. The findings reveal that social media platforms such as WhatsApp, Instagram, and Facebook have been utilized as tools for communication and promotion. However, challenges persist, including limited human resources, concerns over design plagiarism, and irregular content updates. Several MSMEs prefer WhatsApp for its perceived safety and personal engagement, while Instagram usage is restricted to preserve the exclusivity of handmade and limited-edition products. In terms of ecotheology, MSMEs demonstrate a strong commitment to sustainability through the use of local raw materials such as seashells, clay, rattan, and water hyacinth, as well as traditional production processes free from chemical additives. A notable challenge arises in obtaining eco-friendly product certification, which must be conducted outside the region and incurs additional time and cost. The findings are analyzed using five grand theories: Resource-Based Perspective (RBP) to assess competitive advantage based on local resources; Technology Acceptance Model (TAM) to understand social media adoption; Digital Capability Theory to evaluate internal readiness; Green Export Strategy to highlight sustainability in export practices; and Internationalization Theory to map the process of global market expansion. This study recommends strengthening digital literacy, facilitating green certification, and developing an integrative model that combines spiritual values, technology, and culturally rooted export strategies to enhance the global competitiveness of MSMEs.